(untitled) (Simbiótica. Revista Eletrônica, 2023)
Adaptation to climate change has been acquiring more relevance due to disasters associated with the phenomenon. However, the debate about adaptation has been mostly appropriated by neoliberalism. Considering the concept of Climate Justice and the field of Latin America Political Ecology, this article seeks to promote reflections for the adaptation on the periphery of capitalism, considering the dynamics of power and the injustices that occur in this space. For this, was adopted dialectical materialist method since the Latin America, highlights empirical data from the Brazilian context and the contributions of the Marxist Theory of Dependency. It is concluded that the Latin America Climate Justice Agenda contributes to a critical view of climate science, incorporating the relations of power and dependency between the Global North and the Global South and weaving paths for radical transformations that stimulate the confrontation of the backbone of the climate crisis: neoliberal capitalism.